Circulating Inflammation Markers Partly Explain the Link Between the Dietary Inflammatory Index and Depressive Symptoms - Gialluisi A; Santonastaso F; Bonaccio M; Bracone F; Shivappa N; Hebert JR; Cerletti C; Donati MB; de Gaetano G; Iacoviello L (Dove Medical Press, 2021)
Alessandro Gialluisi,1 Federica Santonastaso,2 Marialaura Bonaccio,1 Francesca Bracone,1 Nitin Shivappa,3,4 James R Hebert,3,4 Chiara Cerletti,1 Maria Benedetta Donati,1 Giovanni de Gaetano,1 Licia Iacoviello1,2 On behalf of the Moli-sani Investigators1Department of Epidemiology and Prevention, IRCCS Neuromed, Pozzilli, Italy; 2Department of Medicine and Surgery, University of Insubria, Varese, Italy; 3Cancer Prevention and Control Program and Department of Epidemiology and Biostatistics, Arnold School of Public Health, University of South Carolina, Columbia, SC, USA; 4Department of Nutrition, Connecting Health Innovations LLC, Columbia, SC, USACorrespondence: Alessandro GialluisiDepartment of Epidemiology and Prevention, IRCCS Neuromed, Via dell´Elettronica, 86077, Pozzilli, ItalyTel +390865915244Email alessandro.gialluisi@gmail.comBackground: Depression is a mood disorder characterized by a high rate of resistance to pharmacological treatments, which has often been linked to chronic inflammation. This can be influenced by different environmental factors, in particular pro-inflammatory diets. However, a mediating role of circulating inflammation has never been observed.Aim: To test the association between a dietary inflammatory index (DII®) and continuous depressive symptoms (adapted version of PHQ9) in an Italian population cohort (N=13,301), along with potential explanatory effect of a composite index (INFLA-score) based on four circulating inflammatory biomarkers: C-reactive protein, granulocyte-to-lymphocyte ratio, platelet and white blood cell counts.Results: Significant positive associations were observed between DII and total depressive symptoms (standardized β (SE) = 0.038 (0.005), p < 0.001), and with two factors tagging somatic (0.012 (0.003), p < 0.001) and cognitive symptoms (0.012 (0.003), p < 0.001), after adjustment for different potential confounders (socioeconomic status, chronic health conditions and lifestyles). These associations were about twice as strong in women than in men. INFLA-score explained a small but significant proportion of the association with total depressive symptoms (0.90- 2.30%, p < 0.05), which was mainly driven by granulocyte-to-lymphocyte ratio (1.18- 1.65%). This effect was even stronger for the somatic (2.66- 4.66%) but not for the cognitive factor (0%).Conclusion: These findings support a strong link between inflammatory diet and depression, especially with somatic symptoms and within women. Moreover, they provide novel evidence for a potential explanatory role of circulating inflammation in this association, suggesting new paths for prevention and treatment of major and atypical depression.Keywords: dietary inflammatory index, depressive symptoms, atypical depression, circulating inflammation, granulocyte-to-lymphocyte ratio, white blood cells